User-centered design for a customized mobile dialysis device for patients with ESRD: an interview study. (November 2019) - McCauley, Zach; Niiyama, Itsumi; Kessler, Larry; Kim, Ji-Eun
Dialysis is performed mostly in-center for patients with End Stage Renal Disease (ESRD) who lose normal functionality of their kidneys. The Center for Dialysis Innovation (CDI) at the University of Washington is developing a mobile dialysis device called the Ambulatory Kidney to Improve Vitality (AKTIV). Existing mobile dialysis devices focus on functionality, paying limited attention to human factors. The goal of the current study is to identify human factors-related recommendations for the wearable, constantly dialyzing device currently being developed. To reach this goal, we interviewed both patients and caregivers to understand their needs and preferred attributes for such a device while performing daily activities. We found that travel, recreation, and physical exercise were key task types for a wearable dialysis device to accommodate. In addition, safety and accuracy were found to be the attributes most important to participants Incorporating human factors considerations into the design of the mobile dialysis device has the potential to improve the quality of life for patients and caregivers.